PEMANFAATAN MEDIA PEMBELAJARAN MATEMATIKA - Zulfikar Zulfikar; Khairul Ismi; Muhsin Muhsin; Mirunnisa Mirunnisa; Zulfa Razi (Universitas Pahlawan Tuanku Tambusai, 2022)
Mathematics is one of the subjects taught in elementary schools in the 2013 curriculum as well as in the Freedom to Learn curriculum which is summarized in Thematic. Mathematics is an abstract object that makes mathematics difficult for some elementary school students to understand. the use of teaching aids as a medium for learning mathematics is expected to help improve students' understanding of mathematical concepts. Therefore, it is very appropriate that lecturers from several universities in Aceh feel compelled to accompany these teachers in seminars on the Utilization of Mathematical Learning Media. This activity aims to increase the capacity of teachers in using mathematics learning media, especially visual aids. The method used is the seminar lecture method. The results of this activity indicate that there is an increase in the knowledge and skills of SD Negeri Pertiwi, and Lambarot teachers in compiling the use of mathematics learning media. Keywords: Media, instructional Media, Media Utilization, Mathematics Learning